DEMOCRACY IN POST-SOVIET KYRGYZSTAN AND TURKMENISTAN - KOKAISL, Petr (CENTRAL ASIA AND THE CAUCASUS, 2008)
The economic impact of globalization usually draws the most attention, while the accompanying aspects, which may include the transformation of an entire culture, are mentioned only secondarily. However, deeper transformational changes occur in culture and the social structure, which also affects changes in an individual’s thinking and reasoning. However, efforts to unify (perhaps slowly and not always as visibly) are also an important aspect of globalization, and these efforts deeply influence culture, particularly in terms of political systems and methods of delegating power. Even here a uniform model has been created—the so-called Western-type democracy, which should be ideally applied at an all-planetary level. It is not always easy to leave the original system and accept a new system. Very often certain matters with little or no interrelation may be misunderstood. This applies to the interdependence among the standard of living, culture, and the political system. Where there have been contacts between two different cultures, there have been comparisons (mostly in the area of material culture). Suddenly members of one culture feel inferior to another culture and want to catch up and achieve the same success. In countries where there is a relatively low standard of living, we can often recognize the effort to adopt a “higher” culture (typically American and Western-European), hoping that by adopting it they will achieve the prosperity they desire. Occasionally, although rarely, we see direct pressure on people to stop wearing their traditional clothing, to wear European- or American-style clothing, to change their eating habits, to wear baseball caps or start watching foreign films. This kind of pressure is usually indirect, whereby people leave their culture quite freely, believing they are not modern or cosmopolitan enough. During this process of accepting foreign models, which is often uncritical, uprooting often occurs and there are attempts to look for substitutions, which can result in various political, religious, and ethical extremes. It is often suggested that precisely “Western democracy” is the necessary base for economic prosperity.